Pengaruh Variasi Latihan Pola Langkah Kaki terhadap Kemampuan Bermain Bulutangkis pada Pemain BARET - Bumboro, Bandung; Sanjaya, Hadad; Nursalim (Jurnal Muara Olahraga, 2024)
The problem that will be studied in this research is whether variations in footstep pattern training have an influence on foot performance. The aim of this research is for the players to know the variations in footstep pattern training and to know the correct and correct footstep movements in playing badminton. The research used is quantitative research with the Quasi Experimental Design research type, which takes place at the UNIMUDA Sorong Bukuminton Field. with 6 players as the subject, the collection technique used was observation, then the data obtained was analyzed using the t-test. From the pretest normality test data, it was obtained with a value of 0.804 > 0.05 and posttest data with a value of 0.167 > 0.05, so the data was normally distributed. The homogeneous test for pretest and posttest data was obtained at 0.104, which means 0.104 > 0.05. The data is homogeneous. And also based on the player's posttest score data, it was found that there was a significant influence between variations in footstep pattern training on the player's foot performance. This can be seen from the average value of the player's foot performance before and after being treated, which was 11.83 to 16.00.